Neunzehnhundertfünfundachtzig : ein historischer Bericht (Hongkong 2036) aus dem Ungarischen von *** - Dalos, György, 1943- (Berlin : Rotbuch, 1982)
Transcribes events that took place a year after George Orwell's "Nineteen eighty-four."
HU OSA 300 - RFE/RL collection
Samizdat and Emigré Publications
Keywords: Hungarian fiction